Management of Information and Infrastructure of Indigenous Community at Royal Belum State Park Using Geographical Information System: A Conceptual Design - Zainon, Othman (School of Business and Management Institut Teknologi Bandung, 2015)
Abstract. Nowadays, an integrated location, descriptive inventory data and geographical information are required for a better decision making in Indigenous community management activities. The management system can improve productivity and to save time, money and man power. Conventional maps and Indigenous inventories on papers or spread sheet are lack of meeting these requirements which are not static and subjected to change rapidly. The Geographic Information Systems (GIS) and Database Management (DBM) System are capabilities and confined in manipulation of location and descriptive data, respectively. A GIS system is chosen in Management Information and Infrastructure of Indigenous Communities because its meets all the requirements that can help the authorities to managed the community. GIS able to manipulate location and descriptive data as well as the relationships between them are dynamic. This paper will discussed briefly the conceptual design of GIS activities and Indigenous community in Royal Belum State Park, Malaysia, then terminology and theoretical concepts of GIS, Indigenous community management and the link between them are reviewed.Keywords: Â Management, information, infrastructure, conceptual design, Indigenous communityÂ